2008
DOI: 10.1186/1477-7525-6-22
|View full text |Cite
|
Sign up to set email alerts
|

Some psychometric properties of the Chinese version of the Modified Dental Anxiety Scale with cross validation

Abstract: Objective: To assess the factorial structure and construct validity for the Chinese version of the Modified Dental Anxiety Scale (MDAS). Materials and methods:A cross-sectional survey was conducted in March 2006 from adults in the Beijing area. The questionnaire consisted of sections to assess for participants' demographic profile and dental attendance patterns, the Chinese MDAS and the anxiety items from the Hospital Anxiety and Depression Scale (HADS). The analysis was conducted in two stages using confirmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
100
7
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(131 citation statements)
references
References 43 publications
22
100
7
2
Order By: Relevance
“…The originally proposed theoretical model of the DAS 14 ( Figure 1) and the two-factor model proposed by Yuan et al 18 ( Figure 2) were found to fit adequately to this Brazilian sample, indicating that this scale can be used to investigate dental anxiety. The decision on which model to use should be based on the objective of the investigation: if the focus is anxiety over dental treatment in general, the Model B is recommended.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The originally proposed theoretical model of the DAS 14 ( Figure 1) and the two-factor model proposed by Yuan et al 18 ( Figure 2) were found to fit adequately to this Brazilian sample, indicating that this scale can be used to investigate dental anxiety. The decision on which model to use should be based on the objective of the investigation: if the focus is anxiety over dental treatment in general, the Model B is recommended.…”
Section: Discussionmentioning
confidence: 89%
“…27,30 Next, the above analyses were performed on specific participant subgroups, based on gender, age, socioeconomic level, and previous unpleasant dental experiences, which are supported by the literature as having a significant impact on dental anxiety. The literature reports that women, 16,17,19 younger patients, 17 patients at lower socioeconomic levels, 5,19 and with previous unpleasant dental experiences 18 present greater anxiety over dental treatment. These findings may reflect a pattern of response that is distinct to the items of the DAS.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the 5-item modified DAS, the construct validity and reliability were asserted in detail (Yuan, Freeman, Lahti, Lloyd-Williams, & Humphris, 2008), however, this process was only carried out for the Chinese version of the instrument. Moreover, the internal consistency, reproducibility and the concurrent validity of the scale were also evaluated (Moore, Berggren, & Carlsson, 1991) in a Danish sample with 155 subjects, who presented an exaggerated fear of dentists.…”
Section: Introductionmentioning
confidence: 99%
“…There are several patient report anxiety scales available 2 and we selected the Modified Dental Anxiety Scale (MDAS) because of its relevance, validity and brevity. 3 The MDAS has been translated into a number of world languages, many of which have published psychometrics (Chinese, 4 Greek, 5 Spanish, 6…”
mentioning
confidence: 99%